A quebra da moldura: reverberação e deslocamento de narrativas plurais no discurso concreto e neoconcreto em Lygia Clark (1954-1959) - Bruno Henrique Fernandes Gontijo (2023)
This research aims to understand the emergence of narratives and the consolidation of a discourse constantly reiterated by Brazilian art critics related to the Brazilian Concrete and Neoconcrete Movements, regularly interpreted through the archetype of European geometric abstractionism in the local cultural scene. The dominant discourse is grounded in its exclusivity and, therefore, any other model of analysis is absented, silenced, and forgotten. The position taken up by the Brazilian movement, one of succession, but also overcoming the European vanguards, disregarded the specificities of the Brazilian and Latin American context, claiming an alternative type of exclusivity and uniqueness against similar proposals in countries like Argentina, Uruguay, and Venezuela. Taking as a reference the work that Lygia Clark (1920-1988) produced during the 1950s, critical texts by Mário Pedrosa (1900-1981) about the artist will be analysed, in addition to articles published by Ferreira Gullar (1930-2016) in the Suplemento Dominical do Jornal do Brasil (SDJB) between the years 1956 and 1961. These inaugural texts present the internal bias of the movements, since they were written by those who actively participated in their creation, on the other hand, they corroborate for the structuring of a version of the history that correlates Brazilian concrete art with the European vanguards and their artists, mainly from the influence of Piet Mondrian (1872-1944). In addition to the ancestry and references to the Dutch painter and Neoplasticism in Lygia Clark's work, it is notable that the artist moves away from Mondrian's assumptions to build an artistic trajectory in the field of poetic singularity. Finally, as a case study and an alternative to the dominant thought, the procedures adopted by Clark in the series “Breaking the frame” (1954) and the paintings with “marco recortado” produced, already in the 1940s, by Argentine and Uruguayan artists, members of the Movimiento Arte Madí, will be confronted. The problem that involves “breaking” the semantic structure of the frame is Lygia Clark's first movement towards Mondrian's utopian project of integrating art and life.